2020
DOI: 10.1111/jce.14582
|View full text |Cite
|
Sign up to set email alerts
|

Slow whole left atrial conduction velocity after pulmonary vein isolation predicts atrial fibrillation recurrence

Abstract: BackgroundAtrial conduction velocity may represent atrial fibrillation (AF) substrate after pulmonary vein isolation (PVI). To elucidate the association between whole left atrial conduction velocity (LACV) and AF recurrence after PVI.Methods and ResultsThis observational study enrolled 279 patients (147 paroxysmal and 132 persistent AF) who underwent PVI alone as an initial AF ablation procedure. After PVI, the left atrium was mapped with a 20‐pole multielectrode in conjunction with the CARTO3 system during 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…In this and our previous study, 12 whole left atrial electrophysiological abnormalities such as an extensive mean regional voltage reduction and a slow left atrial total conduction velocity were shown to be reliable predictors of AF recurrence.…”
Section: Af Substrate Extending To the Whole Left Atriumsupporting
confidence: 69%
See 1 more Smart Citation
“…In this and our previous study, 12 whole left atrial electrophysiological abnormalities such as an extensive mean regional voltage reduction and a slow left atrial total conduction velocity were shown to be reliable predictors of AF recurrence.…”
Section: Af Substrate Extending To the Whole Left Atriumsupporting
confidence: 69%
“…Left atrial conduction velocity was calculated as left atrial anterior conduction distance divided by conduction time between the start (septum) and end of the propagation wave front (lateral mitral annulus) in the left atrium, as reported previously. 12 Anterior conduction distance was measured manually by tracing the pathway of the propagation wave front from the start point to the end point in the anterior left atrium.…”
Section: Whole Left Atrial Electrophysiological Degenerationmentioning
confidence: 99%
“…During an invasive CA, the electrical properties can be directly evaluated. A recent paper has shown that a reduced conduction velocity in the LA is a predictor of AF recurrence after PVI [10]. In the present study, we evaluated the electrical properties in both atria in this study and revealed that the conduction velocity in the RA was also more reduced in the Rec group than in the non-Rec group.…”
Section: Reduced Conduction Velocity and Remodeling In The Atriamentioning
confidence: 59%
“…Mapping points were automatically acquired using the CARTO confidence module with the following settings: cycle length filtering, ±30 ms; localize activation time stability, <3 ms; position stability, <2 mm; as reported previously. 12 Anterior conduction distance was measured manually by tracing the pathway of the propagation wave front from the start point to the end point in the anterior LA. Associations between AF recurrence and mapping parameters representing whole LA electrophysiological degeneration were explored.…”
Section: La Voltage Mappingmentioning
confidence: 99%
“…Following a blanking period of 3 months, they completed outpatient clinical visits and 12-lead ECG monitoring at 1, 3, 6 and 12 months, and 24 h-Holter by using the mean regional voltage at each region and LA total conduction velocity. 12 Mean regional voltage was calculated by averaging 10 points evenly selected across the region. 13 Receiver operating characteristic (ROC) analysis was used to estimate a best cut-off value of mean regional voltage to predict AF recurrence.…”
Section: Post-procedures Follow Upmentioning
confidence: 99%